2023
DOI: 10.1080/21645515.2023.2261176
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of the New York State repeal of nonmedical vaccination exemptions on student enrollment, absenteeism, and school workload: Perspectives from a survey of school administrators

John W. Correira,
Stacy M. Pettigrew,
Rhiannon Kamstra
et al.

Abstract: In June 2019, New York State (NYS) adopted Senate Bill 2994A eliminating nonmedical vaccine exemptions from school entry laws. Since student noncompliance with the law required school exclusion, we sought to evaluate the law’s effects on student enrollment and absenteeism, and school workloads related to its implementation. In November 2019, we sent an electronic survey to NYS (excluding New York City) schools. Due to the COVID-19 pandemic, outreach was curtailed in March 2020 with 525 (14%) of 3,759 eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Fifth, we did not examine whether Senate Bill 2994A was associated with changes in school enrollment. Research in both California and NYS has suggested that students may leave traditional school systems to avoid compliance with strict immunization laws, 23 , 24 which may have implications for the spread of vaccine-preventable diseases in the broader population, despite observed increases in school immunization coverage. Sixth, the study did not evaluate the percentage of students on a pathway to immunization compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we did not examine whether Senate Bill 2994A was associated with changes in school enrollment. Research in both California and NYS has suggested that students may leave traditional school systems to avoid compliance with strict immunization laws, 23 , 24 which may have implications for the spread of vaccine-preventable diseases in the broader population, despite observed increases in school immunization coverage. Sixth, the study did not evaluate the percentage of students on a pathway to immunization compliance.…”
Section: Discussionmentioning
confidence: 99%